2009
DOI: 10.3324/haematol.2009.007708
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dexamethasone regulates interleukin-18 and interleukin-18 binding protein in idiopathic thrombocytopenic purpura

Abstract: | 1603 | Brief Report IntroductionInterleukin-18 (IL-18), a member of IL-1 cytokine family, is a potent interferon-γ (IFN-γ) inducing factor and is synthesized by Kupffer cells in the liver, pancreas, kidney, skeletal muscle, lung, osteoblasts, and keratinocytes.1-3 IL-18 binding protein (IL-18BP) is a constitutively secreted protein able to bind IL-18 with high affinity, providing a potential mechanism whereby IL-18 activity is regulated. 4 Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…As a proinflammatory cytokine, it was upregulated in some autoimmune diseases and often in correlation with disease activity (Migliorini et al, 2010). It is reported that the serum IL-18 concentrations in ITP patients were higher compared with normal controls, which confirmed that IL-18 were involved in ITP pathogenesis (Shan et al, 2009b). For the -607 C/A and -137 G/C polymorphisms to cause transcription factor binding and regulate gene expression (Giedraitis et al, 2001), we speculated that there was a correlation between IL-18 promoter polymorphisms and the clinical implications of ITP.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…As a proinflammatory cytokine, it was upregulated in some autoimmune diseases and often in correlation with disease activity (Migliorini et al, 2010). It is reported that the serum IL-18 concentrations in ITP patients were higher compared with normal controls, which confirmed that IL-18 were involved in ITP pathogenesis (Shan et al, 2009b). For the -607 C/A and -137 G/C polymorphisms to cause transcription factor binding and regulate gene expression (Giedraitis et al, 2001), we speculated that there was a correlation between IL-18 promoter polymorphisms and the clinical implications of ITP.…”
Section: Discussionsupporting
confidence: 59%
“…GCs, as a first-line therapy strategy, were widely used in ITP treatment. The research about the mechanism of GC treatment in ITP patients demonstrated that high-dose dexamethasone administration could downregulate IL-18 expression in ITP patients (Shan et al, 2009b), suggesting that GCs work in ITP patients partly by downregulation of IL-18. Thus, in this study, we also analyzed the association between IL-18 polymorphisms and the clinical responses to GC treatment, but no significant association was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-18 is generally produced by macrophages and induces severe proinflammatory processes via its ability to stimulate Th1 cells and natural killer (NK) cells to secrete large quantities of interferon (IFN)-g [41]. Shan et al [42] showed significantly increased levels of IL-18 and IFN in patients with active ITP, whereas in patients in remission the plasma IL-18 levels were similar to healthy controls. Subsequently, a corresponding increase in the IL-18 antagonist, IL-18 binding protein, was noted in patients in remission [43 ].…”
Section: T Cells and Immune Thrombocytopeniamentioning
confidence: 98%
“…31,32 IL-18BP is induced by IFN-γ, thus establishing a negative feedback loop that can be observed in vitro and in vivo; it has been shown that IL-18BP inhibits the production of IL-18-induced IFN-γ and IL-8 production, the activation of nuclear factor κ-light chain enhancer of activated B cells in vitro and the production of lipopolysaccharide-induced IFN-γ production in vivo. 33 -35 Elevated plasma levels of IL-18BP have been reported in idiopathic thrombocytopenic purpura, 13,14 Crohn's disease, 36 inflammatory bowel disease in children and other diseases. 37 -39 The present study is the first to report on the balance between plasma IL-18 and IL-18BP levels in HSP patients.…”
Section: Il-18 and Il-18 Binding Protein In Henoch-schönlein Purpuramentioning
confidence: 99%